(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
It is well known that the adequacy and effectiveness of supervision over banks’ activities is a key factor in ensuring the stability of the banking system and strengthening confidence in banks. Only strong banking supervision enables the stable operation of the banking and financial system the lifeblood of the economy prevents economic crises, attracts private capital, and further boosts foreign investors’ confidence in the banking and financial system.